La experiencia estética del sonido en el espacio. Un contraste filosófico entre espacio arquitectónico y espacio sonoro - Balbontín, Sofía (Universidade de Santiago de Compostela, 2023)
This article aims to discuss the notion of sound-space based on the aesthetic experience of sound in space, observing the audible principles that build spaces shaped only by sound perception. Two types of sound-spaces are recognized; the invisible spaces built by sound (space-of-sound) and the sound emitted by physical space (sound-of-space). In both cases, auditory perception is the cognitive access to spatial information, however, the first one is recognized from acousmatic listening, while the second one is recognized through the process of echolocation. To address this process, a philosophical contrast is established between architectural-space and sound-space, as well as in the relations that appear between the space-of-sound and the sound-of-space. To approach this discussion, the concepts of "smooth"" and ""striated"" proposed by Gilles Deleuze and Felix Guattari in their book A Thousand Plateaus: Capitalism and Schizophrenia, are taken as basis. From this analysis arises that sound-space not only enhances the aesthetics of listening as a powerful creative tool, but also strikes the disciplinary foundations of architecture, towards incorporating ""perception"" as a material for the production of spatialities."
The aesthetic experience of sound in space. A philosophical contrast between architectural space and sound space
Keywords: Espacio-sonoro; Experiencia estética; Espacio liso; Espacio estriado; Espacio en la arquitectura